Report of the Working Group on Irrigated Agricultural Production for the Formulation of Eighth Five Year Plan (1990-1995) - Planning Commission (Planning Commission, 1989)
The achievements in the agricultural sector of our economy during successive Plans have been impressive and have attracted appreciation both at the national and international levels. These can be attributed to the commitment of successive Governments for improving the quality of rural life, Science and Technology back stop provided by a national agricultural research system is the envy of many developing countries and has been adopted by them, committed administration which has ensured timely availability of production inputs and support services and the last and most important in the chain are the Indian farmers who have been responsive to the new technologies inspite of the limitations of small fragmented holdings and poor resource base. Over, the last 40 years.
Planning Commission Government of India
Planning Commission Government of India